Role of a business analyst in analyzing and designing a fintech-monitoring app for BRAC Microfinance under BRAC IT Services Ltd. - Amin, S M Maisoon Ul (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.